2016
DOI: 10.1007/s00701-016-2924-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of polyetheretherketone (PEEK) cages in combination with posterior pedicel screw fixation in pyogenic spinal infection

Abstract: Use of PEEK cages for interbody fusion is feasible and safe in patients suffering from a pyogenic spinal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
2
27
0
4
Order By: Relevance
“…Recently, many independent studies have shown that instrumented spine surgery for spinal infections is a safe and feasible option. 2,3,[5][6][7][8][9][12][13][14][15] Conversely, spinal stabilization could even promote accelerated healing. 9 The risk of reoperation for infection in patients with instrumentation for spinal infection is ≤ 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many independent studies have shown that instrumented spine surgery for spinal infections is a safe and feasible option. 2,3,[5][6][7][8][9][12][13][14][15] Conversely, spinal stabilization could even promote accelerated healing. 9 The risk of reoperation for infection in patients with instrumentation for spinal infection is ≤ 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The use of metallic interbody cages is not the sole possibility to perform a single-stage procedure without the additional morbidity of an autologous graft. Allografts have also been proposed for patients with poor general condition (52) and the use of PEEK was presented in several publications with satisfying results (12,61,69,72,73). The latter has however been recently associated to allergic reactions which deserve further safety investigation (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, surgical intervention for evacuation of pus via anterior approach and corpectomy of the C4 and C5, iliac crest graft with plate and screws fixation was done [11][12][13][14]. Many are believed nowadays that the cervical epidural abscesses are best managed with bony decompression followed by internal stabilization in purulent osteomyelitis and usually by anterior fusion [5,12,15].…”
Section: Discussionmentioning
confidence: 99%
“…While the need for instrumental stabilization remains questionable when predominant problem is the abscess. In 2016, Shiban et al [11] reported the safety of instrumentation devices of fixation in patients suffering from pyogenic spinal infections [11].…”
Section: Discussionmentioning
confidence: 99%